Analyzing Social Capital Factor for Agrotourism Development: A Case Study of Tambakbaya Village, Banten Province - Nainggolan, Sulastri; Muntasib, E.K.S. Harini; Rachmawati, Eva (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2025)
Research on social capital in tourism development has been widely conducted using various approaches. This study examines the social capital of the Tambakbaya Village community to support the development of Sukabungah Agrotourism. Using a survey method, data was collected over three months (December 2023–February 2024) from community members directly and indirectly involved in agrotourism activities. Confirmatory Factor Analysis (CFA) was conducted using IBM SPSS Version 26. The findings reveal that proactive action is the most significant factor influencing social capital in the community. To strengthen social capital, Sukabungah Agrotourism management should enhance community engagement, build trust among stakeholders, expand social networks, and improve compliance through formal socialization and social media, with support from the local government.